Meningococcal B Vaccination (4CMenB) in Infants and Toddlers - Susanna Esposito; Claudia Tagliabue; Samantha Bosis (Journal of Immunology Research)
Neisseria meningitidis is a Gram-negative pathogen that actively invades its human host and leads to the development of life-threatening pathologies. One of the leading causes of death in the world, N. meningitidis can be responsible for nearly 1,000 new infections per 100,000 subjects during an epidemic period. The bacterial species are classified into 12 serogroups, five of which (A, B, C, W, and Y) cause the majority of meningitides. The three purified protein conjugate vaccines currently available target serogroups A, C, W, and Y. Serogroup B has long been a challenge but the discovery of the complete genome sequence of an MenB strain has allowed the development of a specific four-component vaccine (4CMenB). This review describes the pathogenetic role of N. meningitidis and the recent literature concerning the new meningococcal vaccine.